Eccentricity in Induction Machines—A Useful Tool for Assessing Its Level - Janusz Petryna; Arkadiusz Duda; Maciej Sułowicz (Energies, 2021)
In the condition monitoring of induction machines operating in various industry sectors, the assessment of eccentricity is as important as the assessment of the condition of windings, bearings, mechanical vibrations or noise. The reasons for the eccentricity can be various; for example, rotor imbalance, damage or wear of the bearings, improper alignment of the rotor and the load machine and finally, assembly errors after overhaul. Disregard of this phenomenon during routine tests may result in the development of vibrations transmitted to the stator windings, faster wear of the bearings and even, in extreme cases, rubbing of the rotor against the stator surface and damage to the windings and local overheating of the machine core. On the basis of years of experience in the diagnosis of large induction machines operating in various industries, the article deals with the problem of developing reliable indicators for assessing the levels of commonly accepted types of eccentricity. Starting from field calculations and analyzing various cases of eccentricity, the methodology for determining the indicators for evaluation from the stator current spectrum is shown. The changes in the values of these indices for various cases of simultaneous occurrence of static and dynamic eccentricity are shown. The calculation results were verified in the laboratory. Also shown are three interesting cases from diagnostic practice in the evaluation of high-power machines in the industry. It has been shown that the proposed indicators are useful and enable an accurate diagnosis of levels of eccentricity.